The study of alternative leaching processes on South African gold ores - Youlton, Kirsten Leigh (My University, 2020)
The increasing environmental concern surrounding the use of cyanide and the decreasing applicability of cyanidation to new deposits has led to extensive research on alternative gold extraction techniques. The three alternative techniques that were selected for testing (relative to cyanide) were chloride-hypochlorite, thiourea and thiosulphate. These techniques were evaluated using a number of ores including free milling Witwatersrand and Pilgrim’s Rest samples as well as refractory Fairview, Barbrook and Consolidated Murchison samples. From several leach tests it was evident that chloride-hypochlorite and thiourea leaches are highly reactive, reagent consuming and have limited capacity for gold dissolution in the context of the samples of study. This study established that in addition to being reactive to sulphides (from the highly reactive phases such as pyrrhotite, to the more stable phases such as pyrite and chalcopyrite) they also effect phyllosilicates, a typically stable component in gold leaching. This degree of reactivity is significantly greater than suggested in literature and as such these lixiviants are even more impractical than previously thought. The thiosulphate leaching was significantly less reactive with gangue mineralogy and showed no interaction with even the most reactive sulphides, this is in stark contrast to the literature which consistently details the deleterious potential of sulphide phases. Furthermore, this confirms that any shortfalls with regards to limited leaching results is inherently related to the leaching system and related conditions and is not affected by the gangue mineralogy. Thus, thiosulphate leaching has far greater applicability to sulphide-bearing ores than previously thought. Despite the lack of reactivity with gangue minerals, the overall dissolution achieved using thiosulphate was limited without the addition of a stabilising agent to prevent thiosulphate degradation. The use of a stabilising agent showed major improvements in total dissolution, with a dissolution limit for all samples of approximately 70% of the total available gold. The addition of the stabilising agent glycine was found to have no influence on the non-reactive nature of thiosulphate leaching. This limited gold dissolution is likely to be due to reduced kinetics associated with insufficient reagent concentrations throughout leaching. Other relevant factors such as reagent cost and detoxification considerations still favour the well constrained and optimised method that is cyanidation. Significant work in optimisation of leach conditions and detoxification would be important before major changes in the gold industry could be expected
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020